Het Nederlandse woord even en zijn Tsjechische equivalenten in het paralelle corpus InterCorp - Kateřina Křížová (Brünner Beiträge zur Germanistik und Nordistik, 2016)
This paper presents a description of the meaning of the Dutch word "even" and of its Czech equivalents excerpted from the multilingual parallel corpus InterCorp. It is based upon the analysis of more than 1.500 examples of the usage of "even" (as an adjective, adverb or a modal particle) in the Dutch literary texts, which were translated into Czech. The corpus makes it possible to conduct an analysis of the functioning of "even" in a much wider context than the dictionary equivalents. It also helps to better understand the differences and parallels in both the languages.